2017
DOI: 10.4172/2472-0429.1000e103
|View full text |Cite
|
Sign up to set email alerts
|

Insights for the Inhibition of Cancer Progression: Revisiting Ca2+ and Camp Signalling Pathways

Abstract: This editorial article gives insights for the inhibition of cancer progression. The pharmacological modulation of Ca 2+ /cAMP signalling interaction is also cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In addition, considering the existence of a cAMP efflux system mediated by multiresistant protein transporters: the blockade of adenosine receptors reduces the negative inotropic effect promoted by extracellular adenosine due to cAMP efflux system, altering important intracellular signaling pathways [20,21]. Thus, we have proposed that the pharmacological modulation of the intra and extracellular signaling mediated by cAMP and adenosine could be a new antitumoral strategy in CLL therapy [22][23][24][25][26].…”
Section: Lymphocytic Leukemiamentioning
confidence: 99%
“…In addition, considering the existence of a cAMP efflux system mediated by multiresistant protein transporters: the blockade of adenosine receptors reduces the negative inotropic effect promoted by extracellular adenosine due to cAMP efflux system, altering important intracellular signaling pathways [20,21]. Thus, we have proposed that the pharmacological modulation of the intra and extracellular signaling mediated by cAMP and adenosine could be a new antitumoral strategy in CLL therapy [22][23][24][25][26].…”
Section: Lymphocytic Leukemiamentioning
confidence: 99%
“…In addition, it has been shown that the dysregulation of intracellular signaling pathways mediated by Ca 2+ and cAMP participates in the cancer initiation, tumor formation, tumor progression, metastasis, invasion and angiogenesis. Thereby, proteins involved in these pathways, such as Ca 2+ channels and cAMP-dependent protein kinase (PKA), represent potential drugs targets for cancer therapy [20]. With this concept in mind, some studies showed that drugs able to interfere with the intracellular Ca 2+ signaling such as selective VACCs blockers, as amlodipine, inhibit proliferative response in different cancer cells.…”
Section: The "Calcium Paradox" Discovery and Its Impact In Translatiomentioning
confidence: 99%
“…With this concept in mind, some studies showed that drugs able to interfere with the intracellular Ca 2+ signaling such as selective VACCs blockers, as amlodipine, inhibit proliferative response in different cancer cells. In addition, drugs able to increase the intracellular cAMP levels (cAMP-enhancer compounds), such as PDE 4 inhibitors, have been proposed as potential adjuvant, chemotherapeutic or chemopreventive agents in some cancer types, including hepatocellular carcinoma [20]. Then, the pharmacological modulation of the intracellular signaling mediated by Ca 2+ and cAMP in the cancer cells may represent a new therapeutic strategy for cancer progression.…”
Section: The "Calcium Paradox" Discovery and Its Impact In Translatiomentioning
confidence: 99%
“…In addition, it has been shown that the dysregulation of intracellular signaling pathways mediated by Ca 2+ and cAMP participates in the cancer initiation, tumor formation, tumor progression, metastasis, invasion and angiogenesis. Thereby, proteins involved in these pathways, such as Ca 2+ channels and cAMP-dependent Protein Kinase (PKA), represent potential drugs targets for cancer therapy [24]. With this concept in mind, some studies showed that drugs able to interfere with the intracellular Ca 2+ signaling such as selective CCBs, as amlodipine, inhibit proliferative response in different cancer cells [24][25][26][27].…”
Section: The Interaction Between Ca 2+ and Camp Signalling Pathways Amentioning
confidence: 99%
“…Thereby, proteins involved in these pathways, such as Ca 2+ channels and cAMP-dependent Protein Kinase (PKA), represent potential drugs targets for cancer therapy [24]. With this concept in mind, some studies showed that drugs able to interfere with the intracellular Ca 2+ signaling such as selective CCBs, as amlodipine, inhibit proliferative response in different cancer cells [24][25][26][27]. In addition, drugs able to increase the intracellular cAMP levels (cAMP-enhancer compounds), such as Phosphodiesterase (PDE) 4 inhibitors, have been proposed as potential adjuvant, chemotherapeutic or chemopreventive agents in some cancer types, including hepatocellular carcinoma [28].…”
Section: The Interaction Between Ca 2+ and Camp Signalling Pathways Amentioning
confidence: 99%